Faith and Technology in the Classroom: Measuring the Impact of Digital Tools on Islamic Learning Outcomes - Melysa, Melysa; Falah, Riza Zahriyal (Suhuf: International Journal of Islamic Studies, 2025)
This study aims to determine the effect of a short film-based learning model on students’ mastery of Islamic Education material at State Vocational High School 3 Jepara. The research is motivated by the need for innovation in Islamic Education so that learning is not only theoretical but also touches students’ affective and contextual aspects. This quantitative study used a survey method with statistical analyses, including validity, reliability, normality, heteroscedasticity, linearity, and simple linear regression, processed through SPSS 23. The population consisted of 385 grade XI students who had implemented a short film project-based learning model. Using the Slovin formula with a 10% margin of error, 80 students were selected randomly through simple random sampling using Microsoft Excel. Data were collected through questionnaires distributed via Google Forms, supported by documentation and teacher interviews. The results indicated that the short film project-based learning model had a significant effect on learning outcomes, with an R Square value of 0.508. This model encouraged students to master Islamic Education materials more deeply, creatively, and practically through producing Islamic-themed films, making learning more meaningful and relevant to 21st-century challenges.